2021
DOI: 10.3390/healthcare9121611
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Presence of White Nails and Mortality among Rural, Older, Admitted Patients: A Prospective Cohort Study

Abstract: White nails are a sign of various physical deteriorations, including poor nutrition, organ damage, and aging. During a physical examination, white nails can be a helpful health indicator in older patients with vague and multiple symptoms. In this prospective cohort study of patients admitted to the Department of General Medicine in a rural community hospital, we investigated the relationship between white nails and patient mortality. Patient data, including age, sex, condition, and bloodwork results, were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The patient's immunocompromised state could have affected the pathophysiology [12]. In addition to a history of liver cirrhosis and renal failure, the patient had white nails, which is a predictor of mortality in admitted patients [17,18]. Therefore, the patient's immunocompromised state might have facilitated the dissemination of Candida into the prostate [19].…”
Section: Discussionmentioning
confidence: 99%
“…The patient's immunocompromised state could have affected the pathophysiology [12]. In addition to a history of liver cirrhosis and renal failure, the patient had white nails, which is a predictor of mortality in admitted patients [17,18]. Therefore, the patient's immunocompromised state might have facilitated the dissemination of Candida into the prostate [19].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased pain sensation and poor cognition can make the symptoms of diseases vague and difficult to diagnose. Previous studies in rural areas have shown that low serum albumin levels are associated with high mortality and morbidity [ 20 , 21 , 27 ]. High mortality and morbidity rates might also be caused by misdiagnosis and mistreatment of patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of white nails were characterized by a white appearance of the proximal nails with the absence of a lunula. Color changes in the distal region of nails were excluded from the assessment [5,6]. The nail lunula is eventually diminished in all fingers; however, the lunula of the first finger is often persistent, even in older individuals.…”
Section: Assessment Of White Nailsmentioning
confidence: 99%
“…The nail evaluators were unaware of the endpoints of the patients. To improve the diagnosis of white nails, the family physicians who performed the nail examinations in this study were trained using clinical pictures of white nails from a previous study (Figure 1) [5,6].…”
Section: Assessment Of White Nailsmentioning
confidence: 99%
See 1 more Smart Citation